POMC neurons expressing leptin receptors coordinate metabolic responses to fasting via suppression of leptin levels - Caron, Alexandre; Dungan Lemko, Heather M; Castorena, Carlos M; Fujikawa, Teppei; Lee, Syann; Lord, Caleb C; Ahmed, Newaz; Lee, Charlotte E; Holland, William L; Liu, Chen; Elmquist, Joel K (eLife, 2018)
Leptin is critical for energy balance, glucose homeostasis, and for metabolic and neuroendocrine adaptations to starvation. A prevalent model predicts that leptin’s actions are mediated through pro-opiomelanocortin (POMC) neurons that express leptin receptors (LEPRs). However, previous studies have used prenatal genetic manipulations, which may be subject to developmental compensation. Here, we tested the direct contribution of POMC neurons expressing LEPRs in regulating energy balance, glucose homeostasis and leptin secretion during fasting using a spatiotemporally controlled Lepr expression mouse model. We report a dissociation between leptin’s effects on glucose homeostasis versus energy balance in POMC neurons. We show that these neurons are dispensable for regulating food intake, but are required for coordinating hepatic glucose production and for the fasting-induced fall in leptin levels, independent of changes in fat mass. We also identify a role for sympathetic nervous system regulation of the inhibitory adrenergic receptor (ADRA2A) in regulating leptin production. Collectively, our findings highlight a previously unrecognized role of POMC neurons in regulating leptin levels.